2013
DOI: 10.1039/c3bm60055f
|View full text |Cite
|
Sign up to set email alerts
|

Cell phenotypic changes of mouse connective tissue fibroblasts (L-929) to poly(ethylene glycol)-based gels

Abstract: a Cellular responses to various gels fabricated by photoinitiated crosslinking using acrylated linear and multi-arm poly(ethylene glycol) (PEG)-based and poly(propylene glycol)-b-poly(ethylene glycol) precursors were investigated. While no protein adsorption and cell adhesion were observed on the hydrophilic PEG-based gels, protein adsorption and cell adhesion did occur on the more hydrophobic gel generated from the block copolymer precursor. Murine fibroblast viability on the poly(ethylene glycol)-based gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…Figure a shows that L929 cells remained viable (98%) on the hPG-HPA@5% gel surfaces for a cultivation period of 2 days. Although the round-shaped cell morphology (Figure b) indicates that L929 cells could not adhere to the surface due to the nonfouling characteristics of the gels, cellular viability was not affected during the time of observation, which is in good accord with the published data of other polyglycerol gels. , The mechanism of protein/cell nonfouling effect has not been fully understood until now, but some empiric data indicate that the surface hydrophilicity plays an important role. Interestingly, the Cooper-White group recently invented a simple method to enhance cell adhesion on the cell nonfouling PEG gels by incorporating a peptide fragment of fibronectin (Fn), a protein known to enhance cell adhesion . Inspired by this finding, a cell adhesion study was also performed on hPG-HPA@5% gels with the addition of 360 μg/mL Fn; Figure c showed that cell attachment was then observed on the surface, which is in line with the finding by Cooper-White et al On the other hand, when the degree of HPA substitution of hPG was increased from 5% to 10%, the cells on the gel surface were still highly viable (99%) for a 48 h cultivation period (Figure d).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Figure a shows that L929 cells remained viable (98%) on the hPG-HPA@5% gel surfaces for a cultivation period of 2 days. Although the round-shaped cell morphology (Figure b) indicates that L929 cells could not adhere to the surface due to the nonfouling characteristics of the gels, cellular viability was not affected during the time of observation, which is in good accord with the published data of other polyglycerol gels. , The mechanism of protein/cell nonfouling effect has not been fully understood until now, but some empiric data indicate that the surface hydrophilicity plays an important role. Interestingly, the Cooper-White group recently invented a simple method to enhance cell adhesion on the cell nonfouling PEG gels by incorporating a peptide fragment of fibronectin (Fn), a protein known to enhance cell adhesion . Inspired by this finding, a cell adhesion study was also performed on hPG-HPA@5% gels with the addition of 360 μg/mL Fn; Figure c showed that cell attachment was then observed on the surface, which is in line with the finding by Cooper-White et al On the other hand, when the degree of HPA substitution of hPG was increased from 5% to 10%, the cells on the gel surface were still highly viable (99%) for a 48 h cultivation period (Figure d).…”
Section: Resultssupporting
confidence: 66%
“…Cells were not only cultured on the gel surface but also encapsulated into hPG-HPA@5% gels in order to assess the possibility of hosting living cells for perspective therapeutic use. After encapsulation for 48 h, 51% cell viability was observed (Figure a), which is expected because of the gel’s nonadhesive property and the confined polymeric networks to suppress cell growth. , Surprisingly, the supplemented Fn greatly enhanced the cell viability up to 99%. Cells inside gels, however, did not spread even with the addition of Fn (Figure b and c) because the loaded cells were strictly restricted within gels.…”
Section: Resultsmentioning
confidence: 89%
“…First of all, it should be noted that we are very aware that cell adhesion, spreading, and migration heavily depend on the chemistry, topography, and elasticity of the biointerface, as we have studied these relationships in great detail during the last several years. …”
Section: Resultsmentioning
confidence: 99%
“…While 3BC-UV, PEG575-UV and 8PEG-UV hydrogels are formed through the same crosslinking method, the chemical structure of 3BC is different from that of the pure PEG-hydrogels PEG575 and 8PEG. The PPG-block in 3BC is much more hydrophobic than PEG-segments, which makes this gel more hydrophobic in comparison to PEG575-UV and 8PEG-UV hydrogels [ 33 ].…”
Section: Resultsmentioning
confidence: 99%